Green Economic Transformation and SDGs Achievement: Evidence from Malaysia - Siti Aishah Binti Omar; Ibrahim bin Idris (IJED: International Journal of Economy Development Research, 2026)
This article aims to analyze the transformation of the green economy in Malaysia in support of the achievement of the Sustainable Development Goals (SDGs). The focus of the study is directed at energy transition policies, the development of green technology, sustainable investment, and their contribution to low-carbon economic growth. This study uses a qualitative-descriptive approach based on literature study by examining policy documents, sustainable development reports, and academic literature related to the green economy in Malaysia. The findings show that Malaysia has demonstrated strategic commitment through the National Energy Transition Roadmap, Malaysia Renewable Energy Roadmap, as well as low-carbon development policies geared towards increasing renewable energy, energy efficiency, and strengthening green industries. However, the implementation of the green economy still faces challenges in the form of dependence on fossil energy, large investment needs, technology gaps, and cross-sectoral policy coordination. This article concludes that green economic transformation in Malaysia is instrumental in accelerating the achievement of the SDGs, especially SDG 7, SDG 8, SDG 9, SDG 12, and SDG 13, but its success is highly dependent on policy consistency, green financing, technological innovation, and private sector participation.